2008
DOI: 10.1177/0731684407084250
|View full text |Cite
|
Sign up to set email alerts
|

PVT Measurement System for Wood Plastic Composite Melt in an Extrusion Process

Abstract: An innovative experimental system is proposed to measure the pressure—specific volume—temperature (PVT) properties of wood—plastic composite (WPC) melt in an extrusion process. The system is based on determining the specific volume by measuring the volume flow rate and mass flow rate of the WPC melt flowing in a capillary die attached to an extruder at each temperature and pressure. The capillary die mounted on an extruder is used to measure the volume flow rate of the melt. The volume flow rate is estimated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…According to the results, using dynamic viscosity for the composites with the high wood contents, the consistency and power law indexes values will converge to those of Method 1; however for the WPCs having low wood contents, using complex viscosity yields closer values to those of Method 1. In another similar research with the same material, for the compcccccosite containing 40 wt% of wood, the value for power law index (n) was obtained as 0.87, 17 which is noticeably high in comparison with those obtained by the other researches. 18 But the results of power law index in the current study for WPCs with different wood contents are closer to the other reported values.…”
Section: Resultsmentioning
confidence: 80%
“…According to the results, using dynamic viscosity for the composites with the high wood contents, the consistency and power law indexes values will converge to those of Method 1; however for the WPCs having low wood contents, using complex viscosity yields closer values to those of Method 1. In another similar research with the same material, for the compcccccosite containing 40 wt% of wood, the value for power law index (n) was obtained as 0.87, 17 which is noticeably high in comparison with those obtained by the other researches. 18 But the results of power law index in the current study for WPCs with different wood contents are closer to the other reported values.…”
Section: Resultsmentioning
confidence: 80%
“…where ρ is the sample density in g/cm 3 , a is the sample weight in air in g, w is the sample weight in water in g, and water ρ is the density of the water in g/cm 3 .…”
Section: Actual Density Measurementmentioning
confidence: 99%
“…Hence, HYP has been used not only for its low lignin content, but also for its potential thermal stability and its strong adhesion when it is bonded with hightemperature engineering thermoplastic polymers [3] [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcement filler in thermoplastic composite material was wood flour and thermosetting resin was used as the binder material. The advantage of using thermosetting resin over thermoplastic resin is that they have improved temperature resistance, resistance to deformation, superior mechanical property [51,52]. The additive manufacturing technique offers the advantage of inducing the alignment of fibrous material within a product to enhance the mechanical strength.…”
Section: Glass Fiber Reinforced Compositesmentioning
confidence: 99%